Extraction of ochratoxin A in red wine with dopamine‐coated magnetic multi‐walled carbon nanotubes. Issue 20 (31st August 2017) - Wan, Hong; Zhang, Bo; Bai, Xiao‐Lin; Zhao, Yan; Xiao, Meng‐Wei; Liao, Xun
Abstract: A new, rapid, green, and cost‐effective magnetic solid‐phase extraction of ochratoxin A from red wine samples was developed using polydopamine‐coated magnetic multi‐walled carbon nanotubes as the absorbent. The polydopamine‐coated magnetic multi‐walled carbon nanotubes were fabricated with magnetic multi‐walled carbon nanotubes and dopamine by an in situ oxidative self‐polymerization approach. Transmission electron microscopy, dynamic light scattering, X‐ray photoelectron spectroscopy and vibrating sample magnetometry were used to characterize the absorbents. Ochratoxin A was quantified with high‐performance liquid chromatography coupled with fluorescence detection, with excitation and emission wavelengths of 338 and 455 nm, respectively. The conditions affecting the magnetic solid‐phase extraction procedure, such as pH, extraction solution, extraction time, absorbent amount, desorption solution and desorption time were investigated to obtain the optimal extraction conditions. Under the optimized conditions, the extraction recovery was 91.8–104.5% for ochratoxin A. A linear calibration curve was obtained in the range of 0.1–2.0 ng/mL. The limit of detection was 0.07 ng/mL, and the limit of quantitation was 0.21 ng/mL. The recoveries of ochratoxin A for spiked red wine sample ranged from 95.65 to 100.65% with relative standard deviation less than 8%. The polydopamine‐coated magnetic multi‐walled carbon nanotubes showed a high affinity toward ochratoxin A, allowing selective extraction and quantification of ochratoxin A from complex sample matrixes.